2021
DOI: 10.32604/cmc.2021.013771
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Analysis of Cloud Computing Concepts Based on the Computer Science Ontology

Abstract: Our primary research hypothesis stands on a simple idea: The evolution of top-rated publications on a particular theme depends heavily on the progress and maturity of related topics. And this even when there are no clear relations or some concepts appear to cease to exist and leave place for newer ones starting many years ago. We implemented our model based on Computer Science Ontology (CSO) and analyzed 44 years of publications. Then we derived the most important concepts related to Cloud Computing (CC) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Thus, at the level of consumers in both countries, research hypotheses were validated, that certify that e-commerce consumer satisfaction is significantly influenced by the existence of periodic notification system, the existence of a price comparison tool, the existence of reviews from previous customers, the possibility to use different payment methods, the ease of use of the web platform, the open box delivery option, the existence of product customization feature and the loyalty programs. At the level of the analyzed population in Romania and Moldova, this research confirms the partial results from the literature highlighted previously (Huang and Benyoucef, 2013; Sulastri et al , 2019; Kumar and Johari, 2015; Bressolles and Durrieu, 2011; Choi et al , 2019; Consoli, 2017; Park and Lee, 2009; Anastasiei and Dospinescu, 2018; Lopes et al , 2020; D'Acunto et al , 2020; Ventre and Kolbe, 2020; Khalid et al , 2018; Rasli et al , 2018; Ladkoom and Thanasopon, 2020; Vijai and Nivetha, 2020; Lula et al , 2021; Ahmad and Khan, 2017; eMAG, 2021; ITGalaxy, 2021; Pallant et al , 2020; Guercini et al , 2018; Bourlakis et al , 2018; Tahal, 2014; Ieva and Ziliani, 2017; He et al , 2019). At the same time, this research refutes some aspects found in previous research (Nisarz and Prabhakar, 2017; Phuong and Trang, 2018; Lightner, 2004; Banerjee and Karforma, 2008; Zuo et al , 2013; Siraj et al , 2020; Relas, 2019; Elmorshidy, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, at the level of consumers in both countries, research hypotheses were validated, that certify that e-commerce consumer satisfaction is significantly influenced by the existence of periodic notification system, the existence of a price comparison tool, the existence of reviews from previous customers, the possibility to use different payment methods, the ease of use of the web platform, the open box delivery option, the existence of product customization feature and the loyalty programs. At the level of the analyzed population in Romania and Moldova, this research confirms the partial results from the literature highlighted previously (Huang and Benyoucef, 2013; Sulastri et al , 2019; Kumar and Johari, 2015; Bressolles and Durrieu, 2011; Choi et al , 2019; Consoli, 2017; Park and Lee, 2009; Anastasiei and Dospinescu, 2018; Lopes et al , 2020; D'Acunto et al , 2020; Ventre and Kolbe, 2020; Khalid et al , 2018; Rasli et al , 2018; Ladkoom and Thanasopon, 2020; Vijai and Nivetha, 2020; Lula et al , 2021; Ahmad and Khan, 2017; eMAG, 2021; ITGalaxy, 2021; Pallant et al , 2020; Guercini et al , 2018; Bourlakis et al , 2018; Tahal, 2014; Ieva and Ziliani, 2017; He et al , 2019). At the same time, this research refutes some aspects found in previous research (Nisarz and Prabhakar, 2017; Phuong and Trang, 2018; Lightner, 2004; Banerjee and Karforma, 2008; Zuo et al , 2013; Siraj et al , 2020; Relas, 2019; Elmorshidy, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…),Sulastri et al (2019),Kumar and Johari (2015) H3The possibility to cancel the order in a e-commerce application has a significant impact on e-commerce satisfaction levelLightner (2004),Banerjee and Karforma (2008),Zuo et al (2013) H4The existence of live consultant support has a significant impact on e-commerce satisfaction levelSiraj et al (2020), Relas (2019), Elmorshidy (2013) H5 The existence of price comparators has a significant impact on e-commerce satisfaction level Bressolles and Durrieu (2011), Choi et al (2019), Consoli (2017) H6 The existence of the reviews from previous customers has a significant impact on e-commerce satisfaction level Park and Lee (2009), Anastasiei and Dospinescu (2018), Lopes et al (2020); D'Acunto et al (2020), Ventre and Kolbe (2020) H7 The diversity of payment methods has a significant impact on e-commerce satisfaction level Khalid et al (2018), Rasli et al (2018), Ladkoom and Thanasopon (2020)H8The ease of use of the web platform has a significant impact on e-commerce satisfaction levelNisarz and Prabhakar (2017),Phuong and Trang (2018),Vijai and Nivetha (2020),Lula et al (2021), Ahmad and Khan (2017) H9The existence of package opening on delivery option has a significant impact on e-commerce satisfaction levelRasli et al (2018), eMAG (2021, ITGalaxy(2021)H10The product customization feature has a significant impact on e-commerce satisfaction levelPallant et al (2020), Guercini et al (2018), Bourlakis et al (2018)H11The existence of loyalty programs has a significant impact on e-commerce satisfaction levelTahal (2014),Ieva and Ziliani (2017), He et al…”
mentioning
confidence: 99%
“…In the last two year, CSO supported the creation of many innovative applications and technologies, including ontology-driven topic models (e.g., CoCoNoW (Beck, Rizvi, Dengel, & Ahmed, 2020)), recommender systems for articles (e.g., SBR (Thanapalasingam, Osborne, Birukou, & Motta, 2018)) and video lessons (Borges & dos Reis, 2019), visualisation frameworks (e.g., ScholarLensViz (L öffler et al, 2020), Con-ceptScope (X. Zhang, Chandrasegaran, & Ma, 2021)), temporal knowledge graphs (e.g., TGK (Rossanez, dos Reis, & da Silva Torres, 2020)), NLP frameworks for entity extraction (Dessì, Osborne, Recupero, Buscaldi, & Motta, 2021), tools for identifying domain experts (e.g., VeTo )), and systems for predicting academic impact (e.g., ArtSim (Chatzopoulos, Vergoulis, Kanellos, Dalamagas, & Tryfonopoulos, 2020a)). It was also used for several large-scale analyses of the literature (e.g., Cloud Computing (Lula, Dospinescu, Homocianu, & Sireteanu, 2021), Software Engineering (Chicaiza & Reátegui, 2020), Ecuadorian publications (Chicaiza & Reátegui, 2020)).…”
Section: Topic Detectionmentioning
confidence: 99%
“…Hybrid Cloud: Capacity to adapt to existing technological systems hosted on company premises. This makes it possible for the most critical processes for the business to be carried out locally, while other processes are carried out through the platform [19,33,34].…”
Section: Literature Reviewmentioning
confidence: 99%